Comparative study on the quality of two rice (Oryza sativa) varieties produced under organic and conventional systems - Juanico, Sami Clarisse Tardaguela (2012.)
Randomized Complete Block Design (RCBD) experiment was performed during the late wet season to compare the performance of two commercial rice varieties.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Rice; Oryza sativa